Induced expression of the Fragaria × ananassa Rapid alkalinization factor‐33‐like gene decreases anthracnose ontogenic resistance of unripe strawberry fruit stages. (29th July 2019) - Merino, Maria Cecilia; Guidarelli, Michela; Negrini, Francesca; De Biase, Dario; Pession, Annalisa; Baraldi, Elena
Summary: Rapid alkalinization factor (RALF) genes encode for ubiquitous small peptides that stimulate apoplastic alkalinization through interaction with malectin‐like receptor kinase. RALF peptides may act as negative regulators of plant immune response, inhibiting the formation of the signal receptor complex for immune activation. Recently RALF homologues were identified in different fungal pathogen genomes contributing to host infection ability. Here, FaRALF‐33‐like gene expression was evaluated in strawberry fruits inoculated with Colletotrichum acutatum, Botrytis cinerea, or Penicillium expansum after 24 and 48 h post‐infection. To investigate the role of FaRALF‐33‐like in strawberry susceptibility, transient transformation was used to overexpress it in white unripe fruits and silence it in red ripe fruits. Agroinfiltrated fruits were inoculated with C. acutatum and expression, and histological analysis of infection were performed. Silencing of FaRALF‐33‐like expression in C. acutatum ‐inoculated red fruits led to a delay in fruit colonization by the fungal pathogen, and infected tissues showed less penetrated infective hyphae than in wild‐type fruits. In contrast, C. acutatum‐ inoculated white unripe fruits overexpressing the FaRALF‐33‐like gene decreased the ontogenic resistance of these fruits, leading to the appearance of disease symptoms and penetrated subcuticular hyphae, normally absent in white unripe fruits. The different response of transfected strawberry fruits to C. acutatum supports the hypothesis that the FaRALF‐33‐like gene plays an important role in the susceptibility of fruits to the fungal pathogen C. acutatum .